Beyond Reforms : Structural Dynamics and Macroeconomic Vulnerability - Ocampo, José Antonio (Palo Alto, CA: Stanford University Press, 2012)
The book is organized in two parts. The first part looks at issues of long-term growth and development patterns, and the second part focuses on issues of macroeconomic vulnerability and its social effects. Chapter 1, looks at the determinants of dynamic efficiency in developing countries, which is seen as the result of two basic processes. Chapter 2, looks at the same issue from a slightly different angle: the combined effect of the technological gap relative to developed countries and the propensity to import. Chapter 3, takes as its starting point the inverted-U pattern followed by the share of manufacturing in total employment as a result of the process of structural change generated by increases in per capita income. Chapter 4, analyzes the social effects of structural reforms. Chapter 5, considers the determinants of business cycles. Chapter 6 explores a case of destabilization. Chapter 7, discusses debt sustainability issues; and the last chapter, deals with divergence and growth collapses, and serves to tie together the issues analyzed in both parts of the book.